Cryovoltammetrically probing functional group reductive cleavage: alkyl-sulfur versus aryl-sulfur bond cleavage in an alkyl naphthyl thioether under single electron-transfer is temperature switchable. - Paddon, C; Bhatti, F; Donohoe, T; Compton, R (2006)
A series of single electron-transfer (SET) reactions on a naphthyl thioether have shown that the reductive cleavage mechanism changes at low temperatures and this selectivity is proved using an electrochemical analysis that mimics the SET reaction conditions.